New wave of businesses: Brick to click approach in Malaysia - Ishak N.A.M.; Abidin N.B.; Rajadurai J. (Science Publishing Corporation Inc, 2023)
Having been born into a technologically advanced, wireless internet society, today's younger generation or the Millennial, is in a better position to be nurtured as the new age online businesses. They are well educated, self absorbed, have a strong sense of independence and highly motivated toward their perception of success. As such, the Millennial generation rushes forward with their marketing strategies to start businesses using social media to reach out their existing and potential consumers. While there have been numerous studies about traditional businesses, there has been little academic research focused on Millennial and which skills needed to become online businesses This paper proposed to measure the association between social media analytical skills and online businesses competencies within the Millennial generation. A questionnaire was used whose respondents were 100 online businesses among Millennial. It is hoped that this study will significantly contribute to a higher success rate in new start ups of online businesses for the Millennial generation. This study will not only enable for further advance the knowledge of Millennial but also to identify key aspects of online businesses competency in digital technologies. 2018 Authors.